(untitled) (Journal of the College of Basic Education, 2020)
Brilliant intelligence in the book Nafh al- Tayeb al- Mari After completing the research and taking the final image and after a continuous follow-up of the literary texts of the poets of Andalusia stand a little to retrieve the things reached by the research and the results that emerged from it has begun the search and follow the linguistic meaning intelligent intelligence light-minded and funny and bright teeth and racing fire burning and racing Flap and then move its wings either the conventional meaning has kept the meaning that was limited in the meaning of the intelligence and the speed of the answer.